Analisis Faktor Yang Mempengaruhi Peningkatan Kinerja Pegawai Kejaksaan Negeri Tebing Tinggi - Sipayung, Sotion Adi Retno; Damanik, Sri Winda Hardiyanti; Pardede, Imelda Marthauli (Economic Development Progress, 2023)
This study aims to determine how the Effect of Factor Analysis Affecting the Performance Improvement of Tebing Tinggi Public Prosecutors' Employees. The results showed that, Based on the motivational hypothesis I (X1), it can be seen that tcount (8.488) > ttable (1.663), and the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that (X1) has a significant effect on Performance (Y). Based on the hypothesis of the second hypothesis, namely Competence (X2), it is known that tcount (0.523) < ttable (1.663), and the significance value is 0.603 > 0.05, meaning that the second hypothesis, namely the variable (X2) has no significant effect on performance (Y). The third hypothesis, namely the Role Perception variable (X3), it is known that tcount (1.612) < ttable (1.663), as well as the significance value of 0.001 > 0.05, it means that the third hypothesis, namely the variable (X3) has no significant effect on performance (Y). ). The fourth hypothesis, namely the Organizational Support Perception Variable (X4), it is known that tcount (4.369) > ttable (1.663), as well as the significance value of 0.175 > 0.05, it means that the third hypothesis, namely the variable (X4) has a significant effect on performance (Y).